Comparative Analysis of Business Judgment Rules in Civil Law and Common Law Systems - Sugiarto Sugiarto; Sapta Eka Yanto; Sudiyanto Sudiyanto; Panji Riyadi; Purnomo Purnomo; Royan Siagian; Zainal Arifin Hosein (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study examines the comparative regulation of the Business Judgment Rule (BJR) between countries adopting Civil and Common Law systems. BJR is a principle that grants corporate decision-makers the discretion to make business decisions without fear of legal liability, provided that the decisions are made in good faith, are reasonable, and free from conflicts of interest. This research aims to identify the similarities and differences in the regulation of BJR between civil law and common law countries and analyze the factors contributing to these differences. This research employs a normative juridical method with a legislative and comparative law approach. These approaches are utilized to analyze relevant national and international legislation and compare the application of BJR in Indonesia with that of other countries, such as the United States and European nations. The findings are expected to provide insights into the philosophical and practical differences in the regulation and implementation of BJR across these two legal systems.